Analisis Asosiasi Kultural atas Warna: Sumatera I - Mita Purbasari; R.A. Diah Resita I. Kuntjoro-Jakti (Bina Nusantara University, 2014)
Analysis cultural association of color is an approach to know color from cultural side. Unlike previous studies about color, which see the color from the aspect of psychology, then this color research’s aimed to provide insight local colors based on culture. Johannes Itten’s theory of color is used as the basis theory in this research. The theory will be reflected into the cultures of Indonesia, and in this research represented by Sumatera Island. The scope of cultural colors that will be examined is textile product of traditional clothes, bride, apparel and culinary, because these products are the most closely reflection of a culture in a society where the society defines the identity of its own. This research of a qualitative method covers collecting data of study literature, interviewing the color experts, historians and artists, visiting cultural centers especially that associated with textil and culinary product. The result will be formed of morphological matrix cultural over color. Matrix of analysis will be held in arquement and proposal study, where students can use, cultivate, and maximize method of color in visual communication to achieve the contrast and balance.